'n Eksegese van 'n leksikografiese metode: Die WAT en die probleem van ensiklopedisiteit in die verklarende linguistiese woordeboek - Swanepoel, Piet (Lexikos, 1995)
An Exegesis of a Lexicographic Method: The Woordeboek van die Afrikaanse Taal (WAT) and the Problem of Encyclopedicity in Monolingual Linguistic DictionariesThe WAT has often been criticised for its encyclopedic features. In this article a critical review is given of the metalexicographical points of view from which one of its editors, F.J. Snijman, motivates the so-called "encyclopedic" features of the WAT. Snijman shows convincingly that the problem of the encyclopedic nature of monolingual dictionaries cannot be reduced to a naive confusion between the linguistic meaning and knowledge of the referents of words, but that the "encyclopedic" lexicographical practices of monolingual dictionaries are well motivated, theoretically and pragmatically. It is argued, though, that Snijman does not motivate his own choice of metalexicographical points of view and does not discuss a number of critical issues in enough depth.